'My Special Prayer': on Self, God and Prayer - Zondag, Hessel J.; Van Uden, Marinus H.f (European Journal of Mental Health, 2014)
In this contribution we will demonstrate the impact of narcissism – an important personality trait in individualistic societies – on religious behaviour. Present-day Western culture is generally characterised as being expressive individualistic. A dominant trait in this pattern is the tendency of people to ascribe divine (godlike) characteristics to themselves. Psychologically speaking, we are dealing with narcissism. The various varieties in the spectrum of narcissism show that these attempts to attribute divine characteristics to the self do not always succeed. These individuals fantasise about becoming godlike, but their self-image is too fragile to enable these attempts to be successful. The success of this narcissistic aspiration has effects on religious activities, like praying. Based on earlier empirical research and a case study we show how self-deification, narcissism and prayer are related. Those who succeed in becoming godlike pray in a different manner than those who fail in this effort. The former address their prayers to themselves or an anonymous higher power, the latter address their prayers to a personal God.